A Versatile Pep-CPDs Nanoprobe for Rapid Detection of mTBI Biomarker in Clinical Instances and Safe Fluorescence Imaging In Vivo for Improved Weight-Drop Mouse Model - Shi, Jian; Li, Xingmei; Cavagnaro, María José; Cai, Jifeng; Zhang, Changquan; Li, Na (Frontiers in Bioengineering and Biotechnology, 2022)
Mild traumatic brain injury (mTBI) is the most common form of traumatic brain injury, however, it is the most difficult to be accurately identified in the early stage because of lacking more reliable biomarkers and detection methods. This study proposes a highly efficient system to detect a molecular biomarker for the early diagnosis of mild traumatic brain injury (mTBI). The system was prepared by a lower cytotoxic peptide-modified fluorescent nanoprobe based on carbon polymer dots (pep-CPDs) with outstanding imaging capabilities. In vitro and vivo tests were explored to the efficiency of pep-CPDs, inferring good performances of the cellular fluorescence imaging and vivo imaging of mice. Moreover, the successful application of pep-CPDs, such as in the mTBI biomarker S100-β detection in a novel improved weight-drop mTBI mouse model and human blood samples. Overall, all these results indicate that the pep-CPDs system is sensitive, rapid, low toxicity and dependable for mTBI diagnosis compared with traditional detection methods. It shows great potential in clinical and translational research and practical applications.